Prevalence of Goiter in rural area of Belgaum district, Karnataka - Kamath R; Bhat Vinod; Rao RSP; Das Acharya; Ganesh K; Kamath Asha (Wolters Kluwer Medknow Publications, 2009)
Background: To determine the prevalence of goiter and to study the factors influencing goiter among people of the rural community in Karnataka state, a community based study. Setting and Study Design: A cross sectional study was carried out to find out the prevalence of goiter in a rural community of Belgaum district. The study was conducted by house-to-house survey for a period of one month. Materials and Methods: Two villages (Handiganur and Gundwad) were selected randomly from Belgaum and Raibag taluks of Belgaum district. All the family members in each household were examined for the presence of goiter using WHO criteria. Iodine content of the salt sample obtained from each household was estimated by using spot testing kits. Information regarding the determinants of goiter was collected and recorded in a pre tested proforma. Data collected was analyzed using SPSS statistical packages. Results: The prevalence of goiter among rural population was found to be 16.6%. Goiter of grade 1 was 15.7% and that of grade 2 was 0.9%. Prevalence among males and females were 7.2% and 21.8%, respectively. The prevalence of goiter was highest among adolescents. Estimation of iodine content in the salt sample revealed that 50% of samples had adequate iodine content (> 15 ppm). Multiple Logistic Regression Analysis revealed that females of the age group 10-49 years were independently associated with goiter. Conclusion: Prevalence of goiter was relatively high and therefore constituted a public health problem in this region.